DIABETES MELLITUS TYPE 2 - THE IMPORTANCE OF HEALTH EDUCATION OF PATIENTS: A REVIEW - Pelicic, Damir; Djukic , Vukica (Sanamed, 2025)
Diabetes mellitus (DM) represents a significant public health problem, and Type 2 Diabetes Mellitus (DM2) is the most common form of this disease, accounting for about 90% of all DM cases worldwide. The prevalence of DM2 has reached pandemic proportions, especially in developed countries. Studies have shown that a low level of health literacy among patients with DM2 can be a significant predictor of premature death, disability, and increased healthcare costs. It is important to emphasize patient education to reduce mortality and improve the quality of life for DM2 patients. This review is based on a search of scientific literature, focusing on original research articles and meta-analyses found in scientific databases such as PubMed, SCOPUS, MEDLINE, and SCI Index, all published within the last ten years. The search focused on topics related to the public health issue of DM2 and the health literacy of affected individuals. Key terms used in the search included diabetes mellitus, Type 2 diabetes mellitus, prevention, health education, public health, risk factors, and others. Studies have shown that a low level of health literacy among DM2 patients can significantly increase the risk of premature death and disability, as well as healthcare costs. It is crucial to emphasize patient education to reduce mortality and improve the quality of life for DM2 patients.
Keywords: Diabetes mellitus; risk factors; obesity; cardiovascular disease; prevention; education